An agricultural high school for Ceres - Morkel, CA (School of Architecture, Planning and Geomatics, 2021)
It is essential for this country that a progressive policy shall be adopted in the field of agriculture for it can be said that the agricultural industry of the Republic plays a leading part in the development of its potential resources and is of great importance to the country's wellbeing. It is the backbone of the country's economic structure, being equalled to in importance only by our mining industry.